Using an interference spectrum as a short-range absolute rangefinder with fiber and wideband source. (19th April 2018) - Hsieh, Tsung-Han; Han, Pin
Abstract: Recently, a new type of displacement instrument using spectral-interference has been found, which utilizes fiber and a wideband light source to produce an interference spectrum. In this work, we develop a method that measures the absolute air-gap distance by taking wavelengths at two interference spectra minima. The experimental results agree with the theoretical calculations. It is also utilized to produce and control the spectral switch, which is much easier than other previous methods using other control mechanisms. A scanning mode of this scheme for stepped surface measurement is suggested, which is verified by a standard thickness gauge test. Our scheme is different to one available on the market that may use a curve-fitting method, and some comparisons are made between our scheme and that one.